Enhancing adoption of Online Zakat Payment Systems: a study on technology readiness, perceived risk, and transparency in Malaysia - Ishak, Nisrin Alyani; Abdul Rahman, Rahayu; Meor Zawawi, Maizura; Alwi, Fatimah; Abd Wahab, Roslan; Zakaria, Nor Balkish (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
This study aimed to examine the intention to adopt online zakat payment services in a developing country, specifically focusing on the impact of Technology Readiness attributes, namely optimism and innovativeness as well as individual’s perceived risk and perceived transparency. Data for the study were collected through an online survey completed by 288 zakat payers in Malaysia. The analysis, conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), revealed that both Technology Readiness’s attributes; optimism and innovativeness as well as perceived transparency had a positive and significant influence on the intention to use online zakat payment services. Conversely, perceived risk had a significant negative impact on adoption intention, emphasizing the need to address risk-related concerns to encourage wider usage. Given the limited research on online zakat service adoption, this study makes a valuable contribution to understanding the factors that influence the adoption of online zakat payments. Additionally, the findings provide insights that can guide strategies to enhance the adoption of online zakat services in similar developing country contexts.